Microstructure and modified hydrogen generation performance via hydrolysis of Mg-Nd-Ni alloys. (26th April 2021) - Xie, Lishuai; Ren, Jiahao; Qin, Yaqiu; Wang, Xiaomin; Chen, Fei; Ba, Zhixin
Abstract: Mg–Nd binary and Mg-Nd-Ni ternary alloys with different Nd/Ni contents are successfully synthesized via near equilibrium solidification in the present work. Alternately distributed irregular Mg, stripe-like Mg2 Ni and block-like Mg12 Nd are clearly observed in Mg-Nd-Ni alloys. The morphologies of as-melt alloys are composition dependent. It is found that Mg–Nd binary alloy shows extremely sluggish hydrolysis kinetics and low hydrogen yield in both distilled water and 5% MgCl2 solution. However, Ni can significantly enhance the hydrolysis properties of Mg. The hydrolysis kinetics and conversion rate improve obviously with the increase of Ni in as-melt Mg-Nd-Ni alloys. As-melt ternary alloys with abundant eutectic microstructures show superior hydrolysis performance. In addition, the hydrolysis properties of as-melt alloys in MgCl2 solution are much better than those in distilled water. The conversion rate of Mg-9Nd8Ni (mass%) alloy in 5% MgCl2 solution is as high as 94.7%. After hydrolysis, Mg2 Ni and Mg12 Nd phases are retained. For Mg-9Nd8Ni alloy, both primary Mg crystals and eutectic regions are partially hydrolyzed within only 10 s of hydrolysis in distilled water. This work shows that microstructure optimization is feasible to modify the hydrogen generation performance of Mg-based alloys. Highlights: Mg-Nd-Ni alloys for hydrogen generation are successfully prepared in this work. Ni shows superior catalysis on hydrolysis of Mg than Nd. MgCl2 evidently enhances the hydrolysis kinetics of Mg-Nd-Ni alloys. Both primary Mg and eutectic region can be corroded by distilled water within 10 s.